Schnitzler syndrome: clinical features and histopathology - Dingli D; Camilleri MJ (Dove Medical Press, 2015)
David Dingli,1,2 Michael J Camilleri3 1Division of Hematology, Department of Internal Medicine, 2Department of Molecular Medicine, 3Department of Dermatology, Mayo Clinic, Rochester, MN, USA Abstract: Schnitzler syndrome is a rare and underrecognized syndrome characterized by chronic urticaria, a monoclonal protein, and a variety of other symptoms, including fever, bone pain, organomegaly, and evidence of an acute phase response. Biopsy of an involved area of the skin shows a neutrophilic infiltrate without evidence of vasculitis or hemorrhage. Although the etiology of the syndrome is unknown, current evidence suggests this is an autoinflammatory syndrome. Recognition of this syndrome is critical since it is highly responsive to anakinra. Keywords: neutrophilic urticarial dermatosis, autoinflammatory syndrome, monoclonal gammopathy, neutrophilic dermatosis, anakinra